Excimer laser doping using highly doped silicon nanoparticles. Issue 11 (26th August 2013) - Meseth, Martin; Kunert, Bernd Christian; Bitzer, Lucas; Kunze, Frederik; Meyer, Sebastian; Kiefer, Fabian; Dehnen, Martin; Orthner, Hans; Petermann, Nils; Kummer, Malin; Wiggers, Hartmut; Harder, Nils‐Peter; et al.
<x xml:space="preserve">Abstract</x> Laser doping of crystalline Si (c‐Si) using highly doped Si nanoparticles (NPs) as the dopant source is investigated. For this purpose Si NPs are deposited onto c‐Si substrates from dispersion using a spin coater and subsequently laser annealed by scanning over the sample with a 248 nm line profile excimer laser. Scanning electron microscope (SEM) investigations demonstrate that the laser intensity as well as the oxide concentration in the NP thin film strongly influence the film forming properties of the annealed NPs. Substrate doping is substantiated using electrochemical capacitance voltage (ECV) measurements on realized pn‐junctions. In dependence of the laser fluencies ranging from 0.81 to 2.54 J cm−2, the effective doping depth is determined to be in the range of 50 to 250 nm. The rectifying behaviour of the pn‐ or np‐junctions is verified by current voltage measurements. A homogeneous in‐plane doping distribution realized by the laser doping process is demonstrated on the µm scale by light beam induced current measurements.